Special Criminal Courts and celerity (Special Criminal Courts for crimes of greater offensive potential?) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
Article 2 of Law 9.099 of September 26, 1995, known as the “Special Criminal Courts Law”, states that “The process will be guided by the criteria of orality, simplicity, informality, procedural economy and speed...” and article 62 of the same law states that “The process before the Special Court will be guided by the criteria of orality, informality, procedural economy and speed...”. It is true that this law deals with both civil and criminal courts, so the rule in article 2, already mentioned, would be enough to make one understand that the legislator intended to affect those principles, including speed, to both courts. However, so that there would be no doubt, and even redundantly, the legislator preferred to reaffirm, in article 62, also mentioned above, in Chapter III, which deals with the Special Criminal Courts, the full application of the informing principles set out at the beginning of the Law, even though the principle of simplicity, present in article 2 of the Law, does not appear in the latter article. The principles of orality, simplicity, informality and procedural economy, as adopted by the Law, all converge towards the principle of speed.
Keywords: Special Federal Courts; major offensive potential; celerity